2022
DOI: 10.1186/s13619-022-00153-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome reveals core cell populations and androgen-RXFP2 axis involved in deer antler full regeneration

Abstract: Deer antlers constitute a unique mammalian model for the study of both organ formation in postnatal life and annual full regeneration. Previous studies revealed that these events are achieved through the proliferation and differentiation of antlerogenic periosteum (AP) cells and pedicle periosteum (PP) cells, respectively. As the cells resident in the AP and the PP possess stem cell attributes, both antler generation and regeneration are stem cell-based processes. However, the cell composition of each tissue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…This pattern is in complete accordance with the characteristics of ossification in deer antlers, and it also agree with previous research conclusions regarding the role of RUNX2 in the ossification process of deer antlers [22]. SOX9 and RUNX2 are essential for the differentiation of mesenchymal stem cell-derived osteochondro-progenitors towards chondrogenesis and osteogenesis, respectively, but SOX9 is dominant over RUNX2 function in mesenchymal precursors that are destined for a chondrogenic lineage during endochondral ossification [22]. TWST2 belongs to a class of important transcription factors that inhibit the premature or ectopic differentiation of preosteoblast cells during osteogenesis [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern is in complete accordance with the characteristics of ossification in deer antlers, and it also agree with previous research conclusions regarding the role of RUNX2 in the ossification process of deer antlers [22]. SOX9 and RUNX2 are essential for the differentiation of mesenchymal stem cell-derived osteochondro-progenitors towards chondrogenesis and osteogenesis, respectively, but SOX9 is dominant over RUNX2 function in mesenchymal precursors that are destined for a chondrogenic lineage during endochondral ossification [22]. TWST2 belongs to a class of important transcription factors that inhibit the premature or ectopic differentiation of preosteoblast cells during osteogenesis [23].…”
Section: Discussionsupporting
confidence: 92%
“…Among them, In the middle tissue of deer antlers, RUNX2 expression level starts to increase compared to the 15d stage at 45d, while in the base tissue, its expression level higher than the 15d at 25d. This pattern is in complete accordance with the characteristics of ossification in deer antlers, and it also agree with previous research conclusions regarding the role of RUNX2 in the ossification process of deer antlers [ 22 ]. SOX9 and RUNX2 are essential for the differentiation of mesenchymal stem cell-derived osteochondro-progenitors towards chondrogenesis and osteogenesis, respectively, but SOX9 is dominant over RUNX2 function in mesenchymal precursors that are destined for a chondrogenic lineage during endochondral ossification [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…INSL3 is produced in theca interna cells of ovarian antral follicles, and an essential role has been reported in ovarian follicle maturation in relation to germ cell survival and follicular androgen production 258–260 . In addition, INSL3 has been implicated in regulation of the skeletomuscular system, including bone metabolism in males, where low levels are associated with an increased risk of osteopenia and osteoporosis, 261 and RXFP2 is implicated in kidney function in rats, 216 as well as in horn and antler development in different species 262,263 …”
Section: Insulin‐like (Relaxin)‐family Peptide and Receptor Systemsmentioning
confidence: 99%
“…[258][259][260] In addition, INSL3 has been implicated in regulation of the skeletomuscular system, including bone metabolism in males, where low levels are associated with an increased risk of osteopenia and osteoporosis, 261 and RXFP2 is implicated in kidney function in rats, 216 as well as in horn and antler development in different species. 262,263 Relaxin-3 is considered a neuropeptide in mammals because relaxin-3 mRNA/peptide is highly expressed in GABAergic neurons in the midline pontine tegmental region (nucleus incertus) and in some adjacent areas, including the pontine raphe nucleus, the ventral, and lateral periaqueductal grey, as well as the deep mesencephalic area dorsal to the substantia nigra, in non-human primate, rat, and mouse brain. 205,206,210,217,220,264 RXFP3 is widely expressed in brain areas including the cerebral cortex, hippocampus, septum, thalamus, hypothalamus, and brainstem, and the pattern of expression largely overlaps the efferent projection zones of the nucleus incertus in rat, mouse, and non-human primate.…”
Section: Recent Advances and Current Anatomical And Functional Knowledgementioning
confidence: 99%
“…The isolation and identification of homogeneous ASCs will not only contribute to a more comprehensive understanding of the stem cell biology of ASCs but will also be crucial for clinical trials and stem cell clinical applications involving ASCs. Li et al found that the horn growth-related gene RXFP2 was specifically expressed in ASCs but not in facial periosteal cells (FPC) and may be one of the specific markers of ASCs [ 52 ]. Wang et al [ 53 ] demonstrated that the Nanog RNA expressed by ASCs was a pseudogene.…”
Section: Antler Stem Cellmentioning
confidence: 99%